Antihypercholesterol Activity of Phyllanthus Acidus L. Leaf Extract in Mus musculus Induced by High Fat Diet - Enggarwati, Intan Dwi; Qomariyah, Nur (LenteraBio : Berkala Ilmiah Biologi, 2023)
The pattern of food consumption in society is a factor in hypercholesterolemia and obesity. Phyllantus acidus leaf extract contains antioxidants that have the potential as anti-hyper cholesterol agents. The aim of this research was to identify the effect of Phyllanthus acidus leaf extract on blood cholesterol levels and body weight in hypercholesterol mice. This study was an experimental study with a completely randomized design consisting of six treatment goups (dose I (215 mg/kg BW), dose II (230 mg/kg BW), dose III (245 mg/kg BW), positive control (simvastatin), negative (hypercholesterolemia), and control goup with four repetitions and treatment for 21 days. Cholesterol levels were measured with the ®EasyTouch glucometer on day 0 (after HFD induction), 7th, and 21st day. Weight was measured with digital scales on day 0 (after HFD induction), 7th, 14th, and 21st day. Blood cholesterol levels and body weight were analyzed using the SPSS progam including the Kolmogov-Smirnov, Lavene’s, ANOVA test, and Duncan’s test. The results stated that the administration of dose I, dose II, dose III, and positive control had a significant effect (p<0.05) on cholesterol levels and body weight of mice. Dose III (245 mg/kg BW) was optimal in reducing cholesterol levels and body weight of mice induced by high fat diet.